Redes de saberes em educação e saúde mental: encontro de profissionais com as tecnologias na promoção de modos de aprender e cuidar - Freitas, Cristhiane Marques de (Universidade Federal Rural do Semi-Árido, 2018)
This dissertation is the result of a research of the ways of making-feel-know of professionals in constituting one of the knots in the network of attention, learning and care that weaves in the encounter between education and mental health. The possibility of connecting these Education and Mental Health networks led us to the observation of an initial course carried out to approximate the educational and clinical experience in the following contexts: Specialized Educational Assistance (AEE) held in schools, continuing education meetings promoted by the Center for Educational Technology (NTM) and the mental health experience of the Center for Psychosocial Care of Childhood and Adolescence (CAPSi). The objective of the research was to understand how the AEE, NTM and CAPSi professionals experience processes of self-constitution and composition of the network that involves learning and care of children and adolescents of inclusive education and mental health in the experience of workshops with integration of light technologies, light-hard and hard. I highlight some authors who contributed to this production and construction of knowledge: Humberto Maturana and Francisco Varela helped to understand processes of inventive cognition; Nize Pellanda, Cláudia Freitas, Mariza Eizirik and Virginia Kastrup favored our understanding of the forms of care and learning in human experience; and Gilbert Simondon and Emerson Merhy have broadened their understanding of the technologies and configuration of human life. The research methodology is qualitative in nature, with an emphasis on intervention research, which we have built with education and mental health professionals. The perspective that we adopt considers the methodology in first person, in which we follow modes of coupling with the light technologies, light-hard and hard in the composition of networks and knots that integrate the forms of caring and learning. The experience in workshops as light technologies counted on the participation of education and mental health professionals in the collective interaction, in doing together in the experience of the meetings. The workshops headed meetings in a network of conversations and interactions, with live scenarios, supported by technologies. We work with writing of oral autonarratives of conversations and in the course of the workshops, autonarratives written in forums, composition of the researcher's field diaries and with the organization of visual and auditory documentation of videos and images photographed. The different ways of acting in the language of education and mental health professionals favored the understanding of the processes involved in this movement of the subjects in the "space between" the institutions of Education and Mental Health. Because of this research, or as we come to ask new questions, we have been able to distinguish some changes of coordination of actions in language and emotions. At the interpretation the autonarratives, we could understand that the network constituted the desire to know one another and the emotions of realizing partnerships, studies and collective learning in the connection of clinical and pedagogical knowledge. We perceive the constituting of inventive processes cultivated in the experience and in the interaction with the technologies. In the experience, researcher and all involved in this research recognized the trust and acceptance of the living word, made visible knowledge, knowledge and weaknesses, need to learn in this complex knowledge. The inventive movement of the network was constituted in the continuous process of self-organization, in knowing and living connected in the emergence of the reflection on modes of care and learning with children and adolescents who live in this movement and in the paths between the institutions and CAPSi
Keywords: Rede; Educação Inclusiva; Saúde mental; Tecnologias; Cognição; Network; Inclusive education; Mental health; Technologies; Cognition; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES